Analisa Dan Perancangan Infrastruktur Jaringan Komputer Untuk Mendukung Pengembangan Implementasi Electronic Government (Studi Kasus Pemerintah Kabupaten Sumbawa Barat) - Shinta Esabella; Iskandar Fitri (Sekolah Tinggi Teknik - PLN, 2015)
The purpose of writing is to be able to know the performance of the service based on the parameters of Quality of Service (QoS) in Computer Networking Infrastructure Sumbawa Barat Regency Government, where the research begins with the building in the Existing Scenario Simulator OPNET version 14.5 and Design Simulation results were compared with the design of the new Computer Network Infrastructure , while the process of analysis and design of the network infrastructure is built using Network Dev0elopment Life Cycle (NDLC). In the study, the data was taken based on the results of observation, interview and documentation study, which found problems in the implementation and management of e-Government in Sumbawa Barat Regency Government in the form of Condition Data exchange within and between SKPD up to this time using the media of the use of the Internet Service Provider and Computer Network Infrastructure as a whole has not been integrated. Results of the comparison Existing and Simulation Design Simulation in 3 test scenarios, simulation results show that the design has a delay, jitter and packet end to end delay is low and a high response time. Thus concluded in this study, that by using Computer Network Infrastructure Design new ones can provide convenience in the development of e-Government applications.